Investigating the Effect of Attachment Style on Suicidal Tendency and Psychological Well-Being: the Moderating Role of Resilience Among Adolescents - Hosseinpour, Nasrin; Shabanian, Mohadeseh; Darabi, Rezvan; Farrokhfal, Fatemeh; Rouhi Khorasani, Nafise (Iranian Journal of Neurodevelopmental Disorders, 2024)
Purpose: The purpose of the current research is to investigate the effect of attachment style on the tendency to commit suicide and psychological well-being with a moderating role of resilience among adolescents who refer to counseling centers in Tehran. Methodology: The current research utilized a descriptive-correlational and cross-sectional research method, employing structural equation modeling (SEM). The research’s statistical population comprised all adolescents who sought counseling in Tehran between July and November 2023. A sample of 146 adolescents was selected using purposive sampling. Research tools included Revised Adult Attachment Scale (RAAS), Beck Scale for Suicidal Ideation (BSSI), Ryff’s Psychological Well-Being Scales (PWB) and Connor-Davidson resilience scale (CD-RISC). Jamovi version 2.4.14 software was used to perform descriptive statistics and evaluate the effect of the moderating variable, and SmartPLS version 4 software was used to analyze the path between variables. A significance level of 0.05 was considered. Findings: Based on the results of the present study, the Anxious attachment component had a negative and significant effect on Autonomy (β=-0.270, P=0.000). Similarly, Anxious attachment component had a negative and significant effect on Positive relationship with others (β=-0.310, P=0.000). Conclusion: The findings of this study suggest that both attachment styles and resilience have a significant impact on influencing suicidal thoughts and psychological well-being. These insights could be valuable for parents, mental health professionals, and family counselors, helping them to better understand the psychological well-being and attachment styles of adolescents.